DETERMINAN PENERIMAAN PENDAPATAN PAJAK DAERAH KOTA SAMARINDA - Muhammad Kadafi, SE., M.SA; Nyoria Anggraeni Mersa; Hanna Septiana Putri (Jurnal Eksis, 2020)
This study aims to determine the effect of GRDP, population and inflation on regional tax revenues both partially and simultaneously. The analytical tool used is multiple linear regression. The data used are GRDP (Gross Regional Domestic Product), Total Population, Inflation and Regional Taxes for 2009-2019. The results of this study partially show that the GRDP has a positive and significant effect on regional tax revenue, the population has a positive and significant effect on regional tax revenue and inflation has a positive but positive effect. significant impact on the acceptance of regional taxes Samarinda. Then together (simultaneously) GRDP, population and inflation have a significant effect on local taxes Keywords: GRDP, Population Amount, Inflation and Regional Tax Revenue in Samarinda City.